(untitled) (Research, Society and Development, 2023)
Objective: To construct a flowchart for the emergency treatment of cardiovascular events in patients with Left Ventricular Assistance Devices. Methodology: A methodological study was carried out to develop the flowchart for emergency cardiovascular treatment in patients using Ventricular Assistance Devices based on an integrative review of the literature from the Virtual Health Library, PubMed, Scopus, Cinahl, and Web of Science, without a defined time frame until February 2023. Result: Three articles with the highest scientific evidence on cardiopulmonary resuscitation in patients with Left Ventricular Assistance Devices implants were found, suggesting the safety of chest compressions in emergency cardiovascular treatment of these patients. The flowchart was constructed using the literature review articles, adapted to the reality of Brazilian hospitals. Conclusion: The treatment of patients with ventricular assistance devices requires knowledge and preparation from the multidisciplinary team to avoid delaying the identification and decision-making process. Further studies with stronger methodological relevance are necessary to ensure the effectiveness of professional conduct and to ensure the safety of the patient.